GAMBARAN TINGKAT KECEMASAN DAN PERSEPSI MAHASISWA DALAM MENGHADAPI TUGAS AKHIR DI PROGRAM STUDI S1 KEPERAWATAN STIKES MUHAMMADIYAH CIAMIS - Rosmiati, Rosmiati; Sriyanti, Yanti; Munandar, Aris (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2022)
The problem that arises when a student faces a thesis for no apparent reason is that some students feel anxious because they think that a thesis is something difficult to do. Sometimes this feeling of anxiety arises before the student tries to work on each stage of the thesis preparation. Anxiety affects student learning outcomes, because anxiety tends to produce confusion and distortion of perception. The method in this study is descriptive, which is research conducted to determine the value of independent variables, either one or more variables (independent) without making comparisons, or connecting with other variables. The population in this study were all final year students in the Nursing Science Study Program of STIKes Muhammadiyah Ciamis as many as 62 people. Sampling in this study used a total sampling technique, namely the entire population was used as a research sample. The results showed that the anxiety level of students in facing the final project was mostly anxious as many as 26 people (41.9%), and the perception of the final project in the Nursing Study Program of STIKes Muhammadiyah Ciamis was mostly positive as many as 34 people (54.9%). Most of them were positive, namely 34 people (54.8%).